Evaluasi Program Pemuliaan Sapi Bali Jantan di Sekolah Peternakan Rakyat Maju Bersama Kabupaten Musi Banyuasin - Apri Irianto; Nurcholis Nurcholis (Musamus Journal of Livestock Science, 2022)
Musi Banyuasin is one of the regency in South Sumatra Province. The population of cattle based on 2017 data is 31,834 heads spread across 14 districts. The type of cattle that is mostly kept is Bali cattle which are scattered throughout the Musi Banyuasin. SPR Maju Bersama is one of the SPRs under the guidance of IPB University in Musi Banyuasin. The purpose of this study was to evaluate the male Bali cattle breeding program at SPR Maju Bersama. The method used in this study is purposive sampling with the observed parameters, namely the pattern of maintenance, the mating system of male sires and the relationship between the rearing system and the results of the livestock BCS assessment as a program evaluation parameter. The results of this study indicate that SPR Maju Bersama is quite good in carrying out the male Bali cattle breeding program as superior breeds. The BCS value is at a score of 3 with a total of 53 heads from the total sample population of 89 heads.